Investigasi Kesalahan Siswa dalam Menyelesaikan Soal Cerita pada Materi Operasi Hitung Bilangan Bulat - Possumah, Brazil Vargas Junior; Rofiki, Imam (Universitas Negeri Surabaya, 2024)
Problem-solving activities in mathematics learning are usually realized through solving word problems. Students' difficulties in solving word problems can lead to errors. This research was conducted with the aim of describing the types of mistakes made by class VII A students of SMP Negeri 1 Dau in solving story questions on integer arithmetic operations using the Newman Error Analysis (NEA) procedure. This research uses a descriptive analysis method. The data collection technique used in this study is the test method. The type of test given is a written test with three word problems in the form of material descriptions on integer arithmetic operations. Based on the results of the analysis, it was found that the mistakes that students often make in solving word problems on integer arithmetic operations are transformation errors (transformation), process skill error (process skill), and errors in writing the final answer (encoding).